Students’ Perception on the Teacher’s Teaching Strategies in English Online Learning During Covid-19 Pandemic at Second Grade Student of SMA Negeri 3 Palopo - Andi Mangnguntungi Sudirman; Rusdiana Junaid; Asmiati B (Didaktika: Jurnal Kependidikan, 2021)
This research aimed to figure out (1) the teacher’s teaching strategies in English online learning during COVID-19 pandemic at second grade students of SMA Negeri 3 Palopo, (2) the students’ perception on the teacher’s teaching strategies in English online learning during COVID-19 pandemic at second grade students of SMA Negeri 3 Palopo. The method used was the application of the mixed method, through an online questionnaire to 31 respondents and also interviewed the English teacher. Data has been analyzed using description qualitatively and statistical analysis. The results of this research indicate that the strategies were applied in English online learning by the English teacher were virtual or video conferences via Zoom or google meet with lecture method in explaining the material. Besides that, the English teacher also applied online chat via Whatsapp group to give assignments and further discussion. Based on the data through the questionnaire, students’ answers of agree which dominated the questionnaire. In addition, the overall result of the research stated that students of SMAN 3 Palopo have positive perception on their teacher’s teaching strategies in English online learning during COVID-19 pandemic with mean score 50,19.